P-type gan ohmic contact structure, method of making and use thereof

CN117134190BActive Publication Date: 2026-10-09SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311342840.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2026-10-09
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

现行方法针对杂质控制主要依赖于调控反应室压强,但该方式对单独杂质的浓度其实很难进行控制,可能会对受主进行补偿、降低空穴浓度,增加制备良好欧姆接触的难度

Benefits of technology

[0005]The purpose of this invention is to provide a method for preparing and applying a P-type GaN ohmic contact structure, which can reduce the specific contact resistivity and improve the performance of the P-type GaN ohmic contact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117134190B_ABST
    Figure CN117134190B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a P-type GaN ohmic contact structure, a P-type GaN ohmic contact structure and application. The Mg-doped P-type GaN ohmic contact performance is regulated and optimized by combining the growth of an epitaxial layer with carbon ion implantation. Specifically, the Mg-doped P-type GaN is first epitaxially grown, then a certain concentration of carbon ions is implanted into the Mg-doped P-type GaN layer by ion implantation after the growth, and the carbon concentration is precisely regulated, the specific contact resistivity is reduced, and then annealing and metal electrode deposition are performed. The method makes the carbon ions assist the carrier to perform the variable-range hopping by being a deep energy level defect with a suitable concentration, reduces the specific contact resistivity, and improves the P-type GaN ohmic contact performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor device technology, and in particular to a P-type GaN ohmic contact structure, its preparation method, and its application. Background Technology

[0002] Gallium nitride (GaN)-based materials (including GaN, AlN, InN, and their alloys) are the third generation of semiconductors after silicon and gallium arsenide, with a bandgap ranging from 0.7 to 6.2 eV. They have broad application prospects and research value in optoelectronics and microelectronics. GaN-based lasers, as a type of GaN-based optoelectronic device, have advantages such as small size, high efficiency, long lifetime, and fast response speed, and have very important application value in both military and civilian fields.

[0003] To obtain high-efficiency GaN devices, optimizing the performance of p-type GaN ohmic contacts is a crucial technical challenge that must be overcome. Because GaN-based lasers experience high current densities during operation, the metal-semiconductor contact at the electrodes is particularly important, typically requiring a specific contact resistivity as low as 10⁻⁶. -5 Ω·cm 2 The doping concentration of Mg is on the order of magnitude, and obtaining high-quality P-type GaN ohmic contacts is a significant challenge. This is mainly because the ionization energy of the P-type impurity Mg is relatively high, resulting in a low ionization probability of Mg at room temperature. This makes it difficult to obtain P-type GaN materials with high hole concentrations. The current mainstream method is to increase the Mg doping concentration to 10⁻⁶. 20 The above-mentioned quantities are used to grow P-type GaN using Metal-Organic Chemical Vapor Deposition (MOCVD). However, MOCVD often introduces certain concentrations of impurities and defects, such as hydrogen and carbon. The passivation effect of hydrogen impurities is difficult to eliminate, mainly requiring oxygen-containing atmosphere thermal annealing to activate Mg. Carbon impurities, as another deep-level defect besides Mg, are closely related to the range-hopping mechanism, and their concentration changes have a significant impact on ohmic contacts. Current methods for impurity control mainly rely on adjusting the reaction chamber pressure, but this method is difficult to control the concentration of individual impurities, potentially leading to acceptor compensation and reduced hole concentration, further complicating the fabrication of good ohmic contacts. Therefore, it is urgent to solve these problems to obtain efficient P-type GaN ohmic contacts, thereby reducing device operating voltage and improving performance.

[0004] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing and applying a P-type GaN ohmic contact structure, which can reduce the specific contact resistivity and improve the performance of the P-type GaN ohmic contact.

[0006] To achieve the above objectives, embodiments of the present invention provide a method for fabricating a P-type GaN ohmic contact structure, comprising: growing an epitaxial layer on a substrate, the epitaxial layer comprising a Mg-doped P-type GaN layer at the top layer; performing carbon ion implantation and annealing on the Mg-doped P-type GaN layer; and fabricating a metal electrode on the surface of the Mg-doped P-type GaN layer.

[0007] In one or more embodiments of the present invention, the epitaxial layer is grown on the substrate using a molecular beam epitaxy apparatus.

[0008] In one or more embodiments of the present invention, the carbon ions are implanted using an ion implanter.

[0009] In one or more embodiments of the present invention, the injected energy is 30keV-400keV.

[0010] In one or more embodiments of the present invention, the carbon ion implantation concentration is 10. 14 cm -2 ~10 17 cm -2 .

[0011] In one or more embodiments of the present invention, the epitaxial layer is grown in an ultra-high vacuum environment and the raw material for growing the epitaxial layer is a high-purity element with a purity of 6N.

[0012] In one or more embodiments of the present invention, the pressure range of the ultra-high vacuum environment is 10. -10 Torr~10 -11 Torr.

[0013] In one or more embodiments of the present invention, the thickness of the Mg-doped P-type GaN layer is 20 nm to 300 nm.

[0014] In one or more embodiments of the present invention, the doping concentration of Mg in the Mg-doped p-type GaN layer is greater than or equal to 5*10⁻⁶. 18 cm -3 .

[0015] In one or more embodiments of the present invention, the annealing temperature is 300°C-800°C.

[0016] In one or more embodiments of the present invention, the annealing time is 15 min to 60 min.

[0017] In one or more embodiments of the present invention, the annealing atmosphere includes nitrogen.

[0018] In one or more embodiments of the present invention, a metal electrode is prepared on the surface of the Mg-doped P-type GaN layer, comprising: preparing a first metal electrode on the surface of the Mg-doped P-type GaN layer, wherein the material of the first metal electrode includes one or more of Pd, Pt, Ni, Al, and Ti, and the thickness of the first metal electrode is 1 nm to 300 nm; and forming a second metal electrode on the surface of the first metal electrode, wherein the material of the second metal electrode includes Au, and the thickness of the second metal electrode is greater than or equal to 30 nm.

[0019] In one or more embodiments of the present invention, the metal electrode can be prepared using electron beam evaporation or magnetron sputtering.

[0020] In one or more embodiments of the present invention, after the metal electrode is prepared, a secondary annealing treatment is performed. The secondary annealing temperature is 400℃~700℃, the annealing time is 30s~600s, and the annealing atmosphere includes nitrogen.

[0021] In one or more embodiments of the present invention, the epitaxial layer further includes a GaN buffer layer formed on the surface of the substrate, an undoped GaN layer formed on the surface of the GaN buffer layer, and the Mg-doped P-type GaN layer formed on the surface of the undoped GaN layer.

[0022] The present invention also provides a P-type GaN ohmic contact structure, comprising: a substrate; an epitaxial layer formed on the surface of the substrate, the epitaxial layer including a Mg-doped P-type GaN layer at the top layer, wherein a carbon ion implantation region is formed in the Mg-doped P-type GaN layer; and a metal electrode formed on the surface of the carbon ion implantation region of the Mg-doped P-type GaN layer.

[0023] The present invention also provides an application of the P-type GaN ohmic contact structure prepared according to the above preparation method in laser devices.

[0024] Compared with the prior art, the method for preparing a P-type GaN ohmic contact structure according to the present invention precisely controls the carbon ion implantation concentration by ion implantation after the epitaxial layer is grown, so that carbon ions can be used as a deep-level defect-assisted carrier with appropriate concentration to perform variable-range transitions, thereby reducing the specific contact resistivity and improving the performance of the P-type GaN ohmic contact.

[0025] According to the method for preparing a P-type GaN ohmic contact structure according to an embodiment of the present invention, P-type GaN is grown using an MBE device, resulting in extremely low initial concentrations of H and C impurities. This facilitates precise control of the carbon ion implantation concentration by the subsequent ion implanter, thereby improving the ohmic contact performance.

[0026] According to the method for preparing a p-type GaN ohmic contact structure according to an embodiment of the present invention, annealing after carbon ion implantation can repair lattice damage caused by ion implantation. Attached Figure Description

[0027] Figure 1 This is a process flow diagram of a method for preparing a P-type GaN ohmic contact structure according to an embodiment of the present invention.

[0028] Figure 2 This is a schematic diagram of a P-type GaN ohmic contact structure according to an embodiment of the present invention.

[0029] Figure 3 This is a schematic diagram of the transmission ring structure of a P-type GaN ohmic contact structure according to an embodiment of the present invention. Detailed Implementation

[0030] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0031] Unless otherwise expressly stated, throughout the specification and claims, the term "comprising" or its variations such as "including" or "comprises" shall be understood to include the stated elements or components without excluding other elements or other components.

[0032] As mentioned in the background section, existing methods for improving ohmic contacts at gold-semiconductor interfaces often focus on increasing Mg activation rate and improving metal electrode type. However, the impact of carbon content on ohmic contacts is rarely addressed. This is primarily because carbon is a highly concentrated impurity in conventional MOCVD growth, difficult to control completely. While its concentration is often controlled by adjusting the reaction chamber pressure, this method cannot precisely control carbon concentration alone and may alter the content of other elements, potentially compensating for acceptor defects, reducing hole concentration, and increasing the difficulty of fabricating good ohmic contacts. Furthermore, due to the growth mechanism, the concentration of carbon impurities in P-type GaN grown by conventional methods remains consistently high, making precise concentration control impossible. Increasing the Mg doping concentration to a high level can lead to a series of problems, such as decreased carrier mobility and reduced device performance. Using oxygen-containing atmospheres for thermal annealing to treat hydrogen impurities may cause oxidation of the contact metal; for example, Pd, a commonly used contact layer metal in lasers, may be oxidized, increasing resistivity.

[0033] To address the aforementioned technical problems, this invention proposes a method for fabricating a p-type GaN ohmic contact structure. This method combines epitaxial layer growth with carbon ion implantation to regulate and optimize the performance of the Mg-doped p-type GaN ohmic contact. Specifically, Mg-doped p-type GaN is first epitaxially grown. After growth, a specific concentration of carbon ions is implanted into the Mg-doped p-type GaN layer via ion implantation, with precise control of the carbon concentration to reduce the specific contact resistivity. Annealing is then performed, followed by the deposition of a metal electrode. This method allows carbon ions to act as a suitable concentration of deep-level defect-assisted carriers for variable-range transitions, thereby reducing the specific contact resistivity and improving the performance of the p-type GaN ohmic contact.

[0034] like Figure 1 As shown, a method for fabricating a P-type GaN ohmic contact structure according to an embodiment of the present invention includes: s1, growing an epitaxial layer on a substrate, the epitaxial layer including a Mg-doped P-type GaN layer at the top layer; s2, performing carbon ion implantation and annealing on the Mg-doped P-type GaN layer; s3, fabricating a metal electrode on the surface of the Mg-doped P-type GaN layer.

[0035] Step s1 involves growing an epitaxial layer using a molecular beam epitaxy (MBE) apparatus. SIMS (Secondary Ion Mass Spectrometry) data shows that P-type GaN grown using MBE has extremely low initial concentrations of H and C impurities. Leveraging the low C and H impurity concentrations during MBE growth facilitates precise control of the carbon ion implantation concentration during subsequent ion implantation, improving ohmic contact performance. In step s2, carbon ion implantation is performed using a commercially available ion implanter. The aim is to precisely control the carbon ion concentration. The beam intensity of the ion source can be adjusted according to the required concentration conditions. Implantation energy, depth, and angle can all be simulated and optimized using mature simulation software like SRIM, ensuring the carbon ions are positioned appropriately and at a suitable concentration, acting as another deep-level defect auxiliary carrier for range-hopping, thus improving ohmic contact performance. Furthermore, in step s2, annealing is performed in an annealing furnace after ion implantation to repair lattice damage.

[0036] The following section elaborates on the preparation method of the p-type GaN ohmic contact structure of this application to facilitate understanding of the content of this application.

[0037] First, a p-type GaN epitaxial layer 20 is epitaxially grown on substrate 10 using a molecular beam epitaxy (MBE) apparatus. Epitaxial layer 20 includes a GaN buffer layer 21, an undoped GaN layer 22, and a Mg-doped p-type GaN layer 23, grown sequentially. Figure 2As shown. P-type GaN materials were all grown using molecular beam epitaxy (MBE). For p-type materials, the growth chamber of the MBE equipment was an ultra-high vacuum environment (10⁻⁶ m² / 40⁻¹²). -10 Torr~10 -11 The source material (Tor) is a high-purity element (99.9999%), which effectively avoids the introduction of impurities such as C, H, and O, resulting in a single crystal material with extremely high purity. Therefore, it can alleviate the compensation effect of Mg atoms when preparing Mg-doped P-type GaN layers. In this embodiment, the thickness of the Mg-doped P-type GaN layer is 20nm-300nm. The doping concentration of Mg in the Mg-doped P-type GaN layer is greater than or equal to 5×10⁻⁶. 18 cm -3 .

[0038] Secondly, carbon ions are implanted into the Mg-doped P-type GaN layer using an ion implanter to form a carbon ion implantation region 231 in the Mg-doped P-type GaN layer, such as... Figure 2 As shown. Within the carbon ion implantation region, the carbon ion concentration is at a suitable value and within this range, allowing carbon ions to act as another deep-level defect auxiliary carrier for range-hopping, thus improving ohmic contact performance. In this embodiment, the carbon ion implanter performs carbon ion implantation at an implantation energy of 30keV to 400keV, and the carbon ion implantation concentration is 10... 14 cm -2 ~10 17 cm -2 .

[0039] Next, the epitaxial wafer after ion implantation is annealed in an annealing furnace to repair the lattice damage caused by ion implantation. The annealing temperature is 300℃-800℃, the annealing time is 15min-60min, and the preferred annealing atmosphere is nitrogen.

[0040] Finally, a transport ring model is prepared through photolithography, deposition of contact metal electrodes, lift-off, and secondary annealing, followed by contact resistivity testing. The deposition equipment used for the contact metal electrodes can be electron beam evaporation, magnetron sputtering, or other coating equipment. The deposited metal electrodes consist of two layers: the first layer is a first metal electrode, commonly made of one or more of Pd, Ni, Pt, Al, and Ti, with a common thickness of 1 nm to 300 nm. The second layer is a second metal electrode, commonly made of Au, with a thickness generally greater than or equal to 30 nm. When the aforementioned P-type GaN material is used in a laser, the preferred electrode material is Pd / Pt / Au (30 nm / 30 nm / 50 nm).

[0041] The purpose of secondary annealing is to alloy the contact metal electrodes to better form ohmic contacts and reduce the potential barrier. The secondary annealing temperature is 400℃~700℃, the annealing time is 30s~600s, and the preferred annealing atmosphere is nitrogen annealing at 650℃ for 90s. The purpose of the transfer ring (CTLM) is to test the specific contact resistivity; its pattern structure is as follows... Figure 3 As shown, several metal ring patterns with different inner and outer diameters (r / R) are obtained through photolithography and other processes to test the corresponding resistance, calculate the specific contact resistivity, and thus evaluate the quality of the ohmic contact.

[0042] In the above embodiments, carbon ion implantation is achieved using an ion implanter. In other embodiments, carbon can also be implanted via high-temperature thermal diffusion, as long as precise control of the carbon content can be achieved.

[0043] refer to Figure 2 As shown, based on the above-described method for fabricating a p-type GaN ohmic contact structure, this application also proposes a p-type GaN ohmic contact structure, including a substrate 10, an epitaxial layer 20, and a metal electrode 30. The epitaxial layer 20 is formed on the surface of the substrate 10. The epitaxial layer 20 includes a GaN buffer layer 21 formed on the surface of the substrate 10, an undoped GaN layer 22 formed on the surface of the GaN buffer layer 21, and a Mg-doped p-type GaN layer 23 formed on the surface of the undoped GaN layer 22. The thickness of the Mg-doped p-type GaN layer is 20 nm-300 nm. The doping concentration of Mg in the Mg-doped p-type GaN layer is greater than or equal to 5 × 10⁻⁶. 18 cm -3 A carbon ion implantation region 231 is formed within the Mg-doped p-type GaN layer 23. The carbon ion concentration within the carbon ion implantation region 231 is 10. 14 cm -2 ~10 17 cm -2 The metal electrode 30 is formed on the surface of the carbon ion implantation region 231 of the Mg-doped p-type GaN layer 23. The metal electrode includes a first metal electrode and a second metal electrode. The first metal electrode is made of one or more of the following materials: Pd, Pt, Ni, Al, and Ti, and its thickness is 1 nm to 300 nm. The second metal electrode is made of Au, and its thickness is greater than or equal to 30 nm.

[0044] The present invention also provides an application of the P-type GaN ohmic contact structure prepared according to the above preparation method in laser devices.

[0045] Compared with existing technologies, the method for preparing the P-type GaN ohmic contact structure in this invention optimizes the ohmic contact by using a Mg-doped P-type GaN layer grown by MBE followed by ion implantation of carbon into the Mg-doped P-type GaN layer. Taking advantage of the near-zero carbon impurity characteristic of the MBE growth process, the carbon content in the implanted P-type GaN material is precisely controlled using an ion implanter. The carbon implanted in the Mg-doped P-type GaN layer, after annealing, can serve as a second deep-level defect besides Mg, assisting charge carriers in variable-range transitions, thereby reducing the specific contact resistivity. This method is low-cost and does not require a high Mg content, making it a feasible approach to improve ohmic contact performance.

[0046] The p-type GaN ohmic contact structure and its performance of this application will be described in detail below with reference to specific embodiments and corresponding comparative examples.

[0047] Example 1:

[0048] Step 1: Using a molecular beam epitaxy (MBE) apparatus, epitaxially grow P-type GaN material on a sapphire substrate, including a GaN buffer layer, an undoped GaN layer, and a Mg-doped P-type GaN layer grown in one step. The Mg-doped P-type GaN layer has a thickness of 200 nm and a Mg doping concentration of 1 × 10⁻⁶. 19 cm -3 .

[0049] Step 2: Use hydrochloric acid:deionized water (1:3) to acid wash the above epitaxial wafer for 15 minutes. After rinsing with deionized water, use acetone, isopropanol and anhydrous ethanol to sonicate the epitaxial wafer for 10 minutes each. Then rinse with deionized water 5 times and blow dry with a nitrogen gun to ensure that the P-type GaN surface is clean and free of impurities.

[0050] Step 3: Implant carbon ions into the cleaned epitaxial wafer using an ion implanter. The implantation energy is 100 keV, and the carbon ion concentration is 1 × 10⁻⁶. 15 cm -2 .

[0051] Step 4: Place the ion-implanted P-type GaN into a tube annealing furnace / rapid annealing furnace and anneal at 700℃ in a nitrogen atmosphere for 30 minutes to repair the lattice damage caused by ion implantation.

[0052] Step 5: After annealing, the epitaxial wafer is acid-washed for 15 minutes with concentrated sulfuric acid: hydrogen peroxide (7:3), then cleaned with deionized water. The epitaxial wafer is then ultrasonicated for 10 minutes each with acetone, isopropanol, and anhydrous ethanol. Finally, it is cleaned with deionized water 5 times and dried with a nitrogen gun to ensure that the P-type GaN surface is clean and free of impurities.

[0053] Step 6: Perform HMDS (hexamethyldisilazane) pretreatment on the epitaxial wafer surface for 10 minutes, then spin-coat photoresist and dry on a hot plate at 95°C for 90 seconds. Afterwards, use as follows... Figure 3 The designed photomask is photolithographically lithographically applied, then developed in 3038 developer to obtain the transport ring pattern, and then baked on a hot plate at 110°C for 90 seconds to harden the film.

[0054] Step 7: Deposit three metal layers of Pd / Pt / Au (30nm / 30nm / 50nm) on the photolithographically lithographic P-type GaN using an electron beam evaporation device, and then strip it with acetone / NMP solution (N-methylpyrrolidone) to remove residual photoresist. After multiple cleanings, the transport ring metal pattern is obtained.

[0055] Step 8: Perform secondary annealing using a rapid annealing furnace. Anneal the metal pattern of the transfer ring at 650°C in a nitrogen atmosphere for 90 seconds to obtain better ohmic contact.

[0056] Step 9: Use a four-probe system to test the circular transmission ring model, obtain multiple sets of resistivity data, and calculate the specific contact resistivity data.

[0057] Comparative Example 1:

[0058] Step 1: Using a molecular beam epitaxy (MBE) apparatus, epitaxially grow P-type GaN material on a sapphire substrate, including a GaN buffer layer, an undoped GaN layer, and a Mg-doped P-type GaN layer grown in one step. The Mg-doped P-type GaN layer has a thickness of 200 nm and a Mg doping concentration of 5 × 10⁻⁶. 20 cm -3 .

[0059] Step 2: The epitaxial wafer obtained in Step 1 is acid-washed with hydrochloric acid and deionized water (1:3) for 10 minutes. After rinsing with deionized water, the epitaxial wafer is ultrasonically treated with acetone, isopropanol and anhydrous ethanol for 10 minutes each. Then it is rinsed with deionized water 5 times and dried with a nitrogen gun to ensure that the contact interface is clean and free of impurities.

[0060] Step 3: After cleaning, the epitaxial wafer surface undergoes a 10-minute HMDS (hexamethyldisilazane) pretreatment, followed by spin-coating with photoresist and drying on a hot plate at 95°C for 90 seconds. Then, it is used as follows... Figure 3 The designed photomask is photolithographically lithographically applied, then developed in 3038 developer to obtain the transport ring pattern, and then baked on a hot plate at 110°C for 90 seconds to harden the film.

[0061] Step 4: The P-type GaN after photolithography is deposited with three metal layers of Pd / Pt / Au (30nm / 30nm / 50nm) using an electron beam evaporation device, and then stripped with acetone / NMP solution (N-methylpyrrolidone) to remove residual photoresist. After multiple cleanings, the transport ring metal pattern is obtained.

[0062] Step 5: Anneal the metal pattern of the transfer ring in a rapid annealing furnace at 650°C in a nitrogen atmosphere for 90 seconds to obtain better ohmic contact.

[0063] Step 6: Use a four-probe system to test the circular transmission ring model, obtain multiple sets of resistivity data, and calculate the specific contact resistivity data.

[0064] Comparative Example 2:

[0065] Step 1: Using an MOCVD device, an epitaxial growth of a 2 μm n-type GaN layer is performed on the GaN buffer layer of a sapphire substrate, followed by the growth of a 400 nm moderately Mg-doped p-type GaN layer (Mg doping concentration 1 × 10⁻⁶). 18 cm -3 A 40 nm heavily Mg-doped p-type GaN layer was regrown (Mg doping concentration 1 × 10⁻⁶). 19 cm -3 When growing heavily Mg-doped p-GaN layers, the reaction chamber pressure is adjusted (from the normal 100 Torr to 50 Torr). The purpose of adjusting the pressure is to adjust the concentration of carbon impurities.

[0066] Step 2: Clean the epitaxial wafer from Step 1. Then, implant carbon ions into the cleaned epitaxial wafer using an ion implanter at an implantation energy of 100 keV and a carbon ion concentration of 1 × 10⁻⁶. 15 cm -2 .

[0067] Step 3: Place the ion-implanted P-type GaN into a tube annealing furnace / rapid annealing furnace and anneal at 700℃ in a nitrogen atmosphere for 30 minutes to repair the lattice damage caused by ion implantation.

[0068] Step 4: Clean the epitaxial wafer from Step 3. After cleaning, perform HMDS (hexamethyldisilazane) pretreatment on the surface of the epitaxial wafer for 10 minutes. Then spin-coat photoresist and dry it on a hot plate at 95°C for 90 seconds. After that, perform photolithography on the transport ring. Then develop it in 3038 developer to obtain the transport ring pattern. Finally, bake it on a hot plate at 110°C for 90 seconds to harden the film.

[0069] Step 5: Deposit three metal layers of Pd / Pt / Au (30nm / 30nm / 50nm) on the photolithographically lithographic P-type GaN using an electron beam evaporation device, and then strip it with acetone / NMP solution (N-methylpyrrolidone) to remove residual photoresist. After multiple cleanings, the transport ring metal pattern is obtained.

[0070] Step 6: Perform secondary annealing using a rapid annealing furnace. Anneal the metal pattern of the transfer ring at 650℃ in a nitrogen atmosphere for 90 seconds. Then, use a four-probe system to test the circular transfer ring model to obtain multiple sets of resistivity data. Calculate the specific contact resistivity data.

[0071] Conclusion: The specific contact resistivity obtained in Example 1 was 4.5 x 10⁻⁶. -5 Ω·cm 2 Comparative Example 1 showed a specific contact resistivity of 2.1 x 10⁻⁶. -2 Ω·cm 2 Comparative Example 2 showed a specific contact resistivity of 6.3 x 10⁻⁶. -3 Ω·cm 2 .

[0072] As demonstrated by Examples 1, 1, and 2, the ohmic contact structure proposed in this invention exhibits lower resistivity and better contact performance, demonstrating its superiority. In Comparative Example 1, where the Mg doping concentration was increased, the performance degradation primarily stemmed from the decreased carrier mobility and deteriorated electrical performance caused by the high impurity doping concentration. In Comparative Example 2, the MOCVD equipment could not precisely control the carbon concentration during the growth stage by adjusting the chamber pressure, which simultaneously increased the concentration of other impurities, leading to uncontrollable material quality. Although ion implantation was subsequently used, the quantity of implanted ions was far lower than the impurity concentration within the sample itself, resulting in insignificant implantation control and ultimately a decrease in ohmic contact performance.

[0073] This invention optimizes ohmic contacts by using a method of ion implantation of carbon into a Mg-doped P-type GaN layer grown via MBE (Metal-Based Electrolysis). Taking advantage of the extremely low impurity concentration during MBE growth, the carbon content in the implanted P-type GaN material is precisely controlled using an ion implanter. The carbon implanted into the Mg-doped P-type GaN layer, after annealing, can act as a second deep-level defect besides Mg, assisting carriers in variable-range transitions, thereby reducing the specific contact resistivity. This method is low-cost and does not require a high Mg content, making it a feasible approach to improve ohmic contact performance.

[0074] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing a p-type GaN ohmic contact structure, characterized in that, include: An epitaxial layer is grown on a substrate using a molecular beam epitaxy apparatus, the epitaxial layer comprising a Mg-doped P-type GaN layer at the top layer; Carbon ion implantation and annealing are performed on the Mg-doped P-type GaN layer using an ion implanter or high-temperature thermal diffusion of carbon elements. A metal electrode was fabricated on the surface of the Mg-doped P-type GaN layer.

2. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, The implantation energy is 30keV-400keV; and / or, the carbon ion implantation concentration is 10. 14 cm -2 ~10 17 cm -2 .

3. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, The epitaxial layer is grown in an ultra-high vacuum environment, and the raw material used to grow the epitaxial layer is a high-purity element with a purity of 6N.

4. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, The thickness of the Mg-doped P-type GaN layer is 20 nm-300 nm; and / or, the doping concentration of Mg in the Mg-doped P-type GaN layer is greater than or equal to 5 * 10⁻⁶. 18 cm -3 .

5. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, The annealing temperature is 300℃-800℃; and / or the annealing time is 15min-60min; and / or the annealing atmosphere includes nitrogen.

6. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, Fabricating a metal electrode on the surface of the Mg-doped p-type GaN layer includes: A first metal electrode is prepared on the surface of the Mg-doped P-type GaN layer. The material of the first metal electrode includes one or more of Pd, Pt, Ni, Al, and Ti, and the thickness of the first metal electrode is 1 nm to 300 nm. A second metal electrode is formed on the surface of the first metal electrode, the material of the second metal electrode including Au, and the thickness of the second metal electrode being greater than or equal to 30 nm.

7. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, After the metal electrode is prepared, a secondary annealing treatment is performed. The secondary annealing temperature is 400℃~700℃, the annealing time is 30s~600s, and the annealing atmosphere includes nitrogen.

8. The method for preparing the p-type GaN ohmic contact structure as described in claim 1, characterized in that, The epitaxial layer further includes a GaN buffer layer formed on the surface of the substrate, an undoped GaN layer formed on the surface of the GaN buffer layer, and a Mg-doped P-type GaN layer formed on the surface of the undoped GaN layer.

9. A p-type GaN ohmic contact structure, prepared by the method for preparing a p-type GaN ohmic contact structure as described in any one of claims 1-8, characterized in that, include: Substrate; An epitaxial layer is formed on the surface of the substrate, the epitaxial layer including a Mg-doped P-type GaN layer at the top layer, and a carbon ion implantation region is formed in the Mg-doped P-type GaN layer; The metal electrode is formed on the surface of the carbon ion implantation region of the Mg-doped P-type GaN layer.

10. The application of the P-type GaN ohmic contact structure prepared by the preparation method according to any one of claims 1 to 8 in laser devices.

Citation Information

Patent Citations

  • Method for improving ohm of p-type gallium nitride

    CN111446622A